2020
DOI: 10.1007/s10114-020-9156-0
|View full text |Cite
|
Sign up to set email alerts
|

The Extension Degree Conditions for Fractional Factor

Abstract: In Gao's previous work, the authors determined several graph degree conditions of a graph which admits fractional factor in particular settings. It was revealed that these degree conditions are tight if b = f (x) = g(x) = a for all vertices x in G. In this paper, we continue to discuss these degree conditions for admitting fractional factor in the setting that several vertices and edges are removed and there is a difference ∆ between g(x) and f (x) for every vertex x in G. These obtained new degree conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Studies in the past 10 years have shown that these three parameters characterize the vulnerability of a network, the existence of factors and fractional factors which represent the feasibility of data transmission (see Gao et al [19][20][21], and also path factor-a special class of the factor (see Zhou et al 22,23 ). In particular, several network robustness parameter conditions with regard to path factors have been obtained in the recent past 2 years.…”
Section: Motivationmentioning
confidence: 99%
“…Studies in the past 10 years have shown that these three parameters characterize the vulnerability of a network, the existence of factors and fractional factors which represent the feasibility of data transmission (see Gao et al [19][20][21], and also path factor-a special class of the factor (see Zhou et al 22,23 ). In particular, several network robustness parameter conditions with regard to path factors have been obtained in the recent past 2 years.…”
Section: Motivationmentioning
confidence: 99%
“…If S is an empty set, then using (9), we have i(G ′ ) ≥ 1 which contradicts to G is 2-edge-connected. Assume that |S| � 1. en, ε 1 (S) ≤ 1, and hence i(G ′ − S) ≥ 2 in light of (9). We get i(G − S) � 0 since G is 2-edgeconnected.…”
Section: Factor Uniform Graphmentioning
confidence: 84%
“…Some recent advances in graph factors can be referred to Zhou et al [6] and Gao et al [7][8][9]. e main contribution in this work is to study the existence of P ≥2 -factor or P ≥3 -factor in special settings by means of sun toughness parameter.…”
Section: Introductionmentioning
confidence: 99%
“…More recent results on graph factors in various settings can be referred to Gao et al [3,4], Wang and Zhang and Zhou et al [5][6][7][8][9][10], and Zhu et al [11,12].…”
Section: Introductionmentioning
confidence: 99%